A construction Industry Case Factors of commercial banks’ loan eligibility of small businesses in South Africa: a construction industry case: Factors of commercial banks’ loan eligibility of small businesses in South Africa: a construction industry case - Yolande Mtsweni, Lindy Mtsweni (Advances in Social Sciences Research Journal, 2020)
This study determines the factors that affect commercial banks’ loan eligibility of small businesses in the construction industry in South Africa. A multiple case study design and six randomly selected small businesses (i.e., three unsuccessful-declined and three successful-approved loan applicants) were used in this study. The qualitative methodology was applied to interview three senior managers from a commercial bank and six senior officials of the businesses, which had undergone the assessment process. The small enterprise assets finance applications of interviewed clients’ outcomes and the credit scoring outcomes either formal complaint letters or minutes were also evaluated after the credit scoring decision had been made to obtain more in-depth data. The main finding of the study was that client’s relationship, background, character, collateral, capital, capacity and affordability are major factors of loan eligibility of small businesses in South Africa. Of particular importance was that, typical relationship-based term loans were based on a business relationship built over years of lending, allowing for substantial flexibility in loan terms.